Maritime accident analysis using modified HFACS-MA - Eslam A. Youssef; Sameh F. El-Sayed; Said Abdelkader (Maritime Research and Technology, 2023)
Purpose: In a previous endeavor, the authors discussed Human Reliability Assessment (HRA), Human Error Identification (HEI), and accident analysis as the most well-known methods of accident investigation. A general overview of the various analytical models and methodologies was given, outlining the key concepts behind each category, and choosing the HFACS-MA spell out to serve as a starting point for any research in this field. This particular model is a qualitative analytic model that examines both active and latent failures revealed in maritime accident reports. In this paper, a comparative study is presented among three versions of the HFACS-MA model; a benchmarking was made with a US government DoD-HFACS version in order to compare the codes inside each version to ensure the integration of all safety standards. Accordingly, the most suitable version was singled out. Design/Methodology/Approach: The modified Maritime Human Factors Analysis and Classification System (HFACS-MA) was carefully examined as a qualitative analytic model to evaluate active and latent failures stated in the contact accident report, identifying human error as the primary cause. This was done as an example of how the modified (HFACS-MA) may be applied to maritime accident analysis. Findings: The authors modified the HFACS-MA version developed by Kim et al. (2011) that was examined by Kang (2017b), and added one code to it, that is Equipment Design and Specification, code (i.9).   Received: 25 July 2023 Accepted: 17 August 2023 Published: 03 September 2023